2009
DOI: 10.1016/s1474-4422(09)70226-1
|View full text |Cite|
|
Sign up to set email alerts
|

250 μg or 500 μg interferon beta-1b versus 20 mg glatiramer acetate in relapsing-remitting multiple sclerosis: a prospective, randomised, multicentre study

Abstract: Bayer HealthCare Pharmaceuticals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
282
1
12

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 387 publications
(304 citation statements)
references
References 28 publications
9
282
1
12
Order By: Relevance
“…No difference was observed between the groups in number of lesions or clinical relapses. The Betaferon Efficacy Yielding Outcomes of a New Dose (BEYOND) trial randomized RRMS participants in a 2:2:1 fashion to IFNB-1b SC 250 μg QOD vs 500 μg vs GA SC 20 mg daily for three years [48]. Participants and treating physicians were unblinded to treatment assignment, but evaluating physicians remained blinded.…”
Section: Comparator Trialsmentioning
confidence: 99%
See 1 more Smart Citation
“…No difference was observed between the groups in number of lesions or clinical relapses. The Betaferon Efficacy Yielding Outcomes of a New Dose (BEYOND) trial randomized RRMS participants in a 2:2:1 fashion to IFNB-1b SC 250 μg QOD vs 500 μg vs GA SC 20 mg daily for three years [48]. Participants and treating physicians were unblinded to treatment assignment, but evaluating physicians remained blinded.…”
Section: Comparator Trialsmentioning
confidence: 99%
“…As described in previous sections, GA was compared to IFNB-1a SC (REGARD) and IFNB-1b SC (BECOME and BEYOND) [46][47][48] for the treatment of RRMS. Though each study under individual scrutiny had potential reasons for failing to demonstrate GA superiority, it has become accepted practice to consider GA and highdose interferons to have similar clinical efficacy.…”
Section: Comparator Trialsmentioning
confidence: 99%
“…Importantly, there was no evidence that a switch of therapy was related to depressive symptoms; only injection issues or poor response was associated with a change in therapy. It is conceivable that patients discontinued therapy in a way that is related to depres- patients with MS (N = 2447) randomized to IFNβ-1b 500 µg, IFNβ-1b 250 µg, or GA. 21,22 In addition, longterm findings from the PRISMS (Prevention of Relapses and Disability by Interferon β-1a Subcutaneously in Multiple Sclerosis) trial, which prospectively compared the efficacy and safety of two different doses of IFNβ-1a with placebo, found no significant differences in the incidence of depression or depression-related adverse events among patients with MS (N = 560) randomized to IFNβ-1a 22 µg, IFNβ-1a 44 µg, or placebo over time. 23 While BEYOND and PRISMS were not specifically designed to examine depression as an outcome, these results are supportive of the outcomes observed in the current study.…”
Section: Use Of Concomitant Antidepressant Medicationmentioning
confidence: 99%
“…1,11 This study as well as other comparison studies have not supported those earlier findings. [18][19][20][21][22][23] There is mounting clinical evidence that IFNβ therapy is not likely to induce depression in MS patients. 1 Treating depression pharmacologically or with cognitive-behavioral therapy is usually very effective in MS patients.…”
Section: Use Of Concomitant Antidepressant Medicationmentioning
confidence: 99%
“…The aim of this study was not to compare efficacy of the medications, because head-to-head studies have previously confirmed, only the negligible difference among the drugs used [15][16][17] .…”
Section: Discussionmentioning
confidence: 99%